Implementasi Program Habituasi 5 Juz Al-Qur’an dalam Mempermudah Hafalan dan Membentuk Sikap Istiqomah Santri - Gizela Andari, Irene; Inayatul Ilahiyah, Iva (ILJ: Islamic Learning Journal, 2025)
The 5 Juz Al-Qur'an habituation program is implemented at Pondok Pesantren Ittihadul Qur'an Catakgayam Jombang to facilitate the memorization process of students and form an istiqamah attitude in everyday life. The research method used is qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation with the main informants consisting of pesantren caregivers, program teachers, and students. The results showed that 1) The implementation of the 5 juz Al-Qur'an habituation program at Ittihadul Quran Catakgayam Islamic Boarding School aims to form a routine habit of reading and memorizing the Al-Qur'an, deepening understanding of meaning, and applying the teachings of the Al-Qur'an in life to get closer to Allah and improve spiritual quality. 2) This program facilitates memorization and forms an istiqomah attitude of students with structured methods, such as muroqobah, group memorization, and routine assistance, so that students can memorize and practice the teachings of the Qur'an consistently. 3) The supporting factors of this program include the involvement of caregivers, a conducive environment, and a structured schedule, while the inhibiting factors are the psychological difficulties of students, lack of assistance, external disturbances, time constraints, and low internal motivation, which require more efforts to increase the effectiveness of the program.